English English - Adita Maharani; Syaiful Anwar; M. Indra Saputra (Jurnal Bilqolam Pendidikan Islam, 2026)
This study aims to analyze the effect of the application of the SSCS (Search, Solve, Create, and Share) learning model on student learning outcomes in the subject of Islamic Cultural History (SKI) at MTs Darul Huda Bandar Lampung, especially in improving higher-order thinking skills in the cognitive domain C6 (creating). The study used a quantitative approach with a quasi-experimental method through a post-test only control group design. The research sample consisted of two classes, namely class VIII A as the experimental group that implemented the SSCS model and class VIII C as the control group that used conventional learning. The research instrument was a multiple-choice test that had passed validity and reliability tests with a Cronbach's Alpha result of 0.617 indicating an adequate level of reliability. Data analysis was carried out using an independent sample t-test. The results showed a significance value of 0.015 <0.05, so there was a significant difference between student learning outcomes in the experimental class and the control class. This finding proves that the SSCS learning model is effective in improving student learning outcomes in the SKI subject. The novelty of this study lies in the application of the SSCS model in the context of learning Islamic Cultural History which is still rarely studied. In addition to improving learning outcomes, the SSCS model is also able to encourage active student involvement, creativity, problem-solving abilities, and higher-order thinking skills, thus contributing to the development of innovative learning strategies in Islamic education.